2004
DOI: 10.1007/s11746-004-1033-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of soybean and lupin protein concentrates produced by ultrafiltration‐diafiltration

Abstract: Ultrafiltration followed by diafiltration (UF-DF) was evaluated for the production of protein products from partially defatted soybean meal or undefatted lupin (Lupinus albus L.2043N) meal. This study determined the effects of UF-DF on functional properties of the extracted proteins and compared the results with those of protein prepared by acid-precipitation (AP). UF-DF produced only protein concentrates (73% crude protein, dry basis, db), while AP produced protein isolates (about 90% crude protein, db). Soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 18 publications
6
47
6
Order By: Relevance
“…These results with press cake protein extracts are similar to those we observed for pennycress seed meal protein isolates [7]. Foaming properties of the press cake protein extracts also compared favorably with values we reported for soybean protein isolate (131 ml and 95 % remaining foam [33]). In contrast, previous research on canola protein isolate produced by methods similar to ours found that the foaming capacity and stability of the isolates were inferior to the foaming properties of its meal and also declined as the pH increased from 10 to 12 [27,34,35].…”
Section: Foaming Propertiessupporting
confidence: 89%
“…These results with press cake protein extracts are similar to those we observed for pennycress seed meal protein isolates [7]. Foaming properties of the press cake protein extracts also compared favorably with values we reported for soybean protein isolate (131 ml and 95 % remaining foam [33]). In contrast, previous research on canola protein isolate produced by methods similar to ours found that the foaming capacity and stability of the isolates were inferior to the foaming properties of its meal and also declined as the pH increased from 10 to 12 [27,34,35].…”
Section: Foaming Propertiessupporting
confidence: 89%
“…1% b-mercaptoethanol, which had even higher oil content (15% db, Table 1), produced the most stable foam. Its 93% remaining foam almost equaled the foam stability we observed for soybean protein concentrate [30]. We believe that this enhanced foam stability was the result of SDS co-extracted with the protein and not removed thoroughly by dialysis, as was mentioned previously.…”
Section: Foaming Propertiessupporting
confidence: 76%
“…At pH 7, protein from finished germ had a better emulsifying capacity than wet germ protein, as shown by greater EAI values ( Table 2). All the corn germ protein extracts, however, had EAI values that exceeded the 56 m 2 /g protein we determined for soybean protein [30]. At pH 10, all the corn germ protein extracts had EAI values that were significantly greater than those observed at pH 7 ( Table 2).…”
Section: Emulsification Propertiesmentioning
confidence: 49%
“…Higher EAI values indicate better emulsifying capacity. The EAI value at pH 10 for unprocessed Cuphea proteins (Table 2) was more than twice that of low-fat soy flour determined by Heywood et al (18), but 25 and 50% less than the EAI for acid-precipitated lupin and soybean proteins, respectively, reported by HojillaEvangelista et al (19). Heating the flaked seeds (in the conditioner and screw press) increased EAI values by at least 40% (CF75) and as much as 133% (CF120).…”
Section: Resultsmentioning
confidence: 64%
“…The ESI value for unprocessed Cuphea seed protein ( Table 2) was double that observed for acid-precipitated soybean protein (19), which implied that emulsions formed by Cuphea protein were more stable than those formed by soybean protein.…”
Section: Resultsmentioning
confidence: 86%